Photon’s Spin Mechanism and Wave-Particle Hybrid Structure. It Exhibits both Wave Property and Particle Property at the Same Time in all Experiments. - Chen, Sennian (European Journal of Applied Sciences, 2023)
The interpretation of single photon double slits Wheeler’s delayed choice experiment leads to a weird inference: "what the observer does now can change what happened in the past". It subverts our cognitions. Other interpretations are also in dispute. Is there another possible way that can better explain experiments? For this purpose, we try to reacquaint what is a photon? What structure does it have? How does the structure influence the photon behavior? In 1905 Einstein supposed that the photon is a quantum of EM radiation; according to the quantum interpretation, the probability density of a coherent state undergoes a sinusoidal vibration with time. It will also excite a quantized EM wave. So, our research object must be an EM wave beams. We discover and prove that under the Quantification Law of Charge, there is a kind of axial symmetric EM-wave beam it is a quantum of circularly polarized light. Its energy is concentrated in a very small packet; this energy packet will be proved having the photon properties, like , , spin , obeying B-E statistics and so on; On the other hand, the width of the sodium spectral lines identifies that the energy packet carries a long EM wave beam. They form a wave-particle hybrid structure. It exhibits both wave property and particle property at the time in all experiments. Its interpretation for the single photon double slits Wheeler’s delayed choice experiment does not lead to the above strange inference.